Adenosine: an endogenous inhibitor of neutrophil-mediated injury to endothelial cells. - Cronstein, B N (1986)
Since adenosine and its analogue 2-chloroadenosine prevent neutrophils from generating superoxide anion in response to chemoattractants, we sought to determine whether these agents could inhibit neutrophil-mediated injury of endothelial cells. The chemoattractant N-formyl-methionyl-leucyl-phenylalanine (FMLP, 0.1 microM) enhanced the adherence of neutrophils to endothelial cells twofold (18 +/- 2% vs. 39 +/- 3% adherence, P less than 0.001) and caused substantial neutrophil-mediated injury to endothelial cells (2 +/- 2% vs. 39 +/- 4% cytotoxicity, P less than 0.001). 2-Chloroadenosine (10 microM) not only inhibited the adherence of stimulated neutrophils by 60% (24 +/- 2% adherence, P less than 0.001) but also diminished the cytotoxicity by 51% (20 +/- 4% cytotoxicity, P less than 0.002). Furthermore, depletion of endogenously released adenosine from the medium by adenosine deaminase-enhanced injury to endothelial cells by stimulated neutrophils (from 39 +/- 4% to 69 +/- 3% cytotoxicity, P less than 0.001). Indeed, in the presence of adenosine deaminase, even unstimulated neutrophils injured endothelial cells (19 +/- 4% vs. 2 +/- 2% cytotoxicity, P less than 0.001). These data indicate that engagement of adenosine receptors prevents both the adhesion of neutrophils and the injury they cause to endothelial cells. Adenosine inhibits injury provoked not only by cells that have been stimulated by chemoattractants but also by unstimulated cells. Based on this model of acute vascular damage we suggest that adenosine is not only a potent vasodilator, but plays the additional role of protecting vascular endothelium from damage by neutrophils.